2019
DOI: 10.1016/j.mex.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of skeletal age based on Greulich-Pyle method in Tehran

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Consequently, the accuracy of AI BA assessment for children younger than 12 years may be less accurate than that for children aged 12-18 years. In clinical practice, BA assessment for children younger than 12 years is also more difficult for radiologists and endocrinologists, and interobserver variability is more likely to occur (Ebrahimzade et al, 2019;Alshamrani, Messina & Offiah, 2019). Therefore, more training data of left hand radiographs from younger children are helpful to improve the performance of the AI BA system.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the accuracy of AI BA assessment for children younger than 12 years may be less accurate than that for children aged 12-18 years. In clinical practice, BA assessment for children younger than 12 years is also more difficult for radiologists and endocrinologists, and interobserver variability is more likely to occur (Ebrahimzade et al, 2019;Alshamrani, Messina & Offiah, 2019). Therefore, more training data of left hand radiographs from younger children are helpful to improve the performance of the AI BA system.…”
Section: Discussionmentioning
confidence: 99%
“…Precocious puberty was diagnosed based on the following criteria: Breast growth and pubic hair: Breast growth and pubic hair growth were defined as stage 2 or higher according to Tanner [ 19 ]. Bone age: Bone age was measured according to the method presented by Greulich and Pyle [ 20 ]; 2 years above the mean for chronological age is consistent with precocious puberty. Uterine and ovarian dimensions: Trans-abdominal pelvic ultrasound scans were performed with a conventional full-bladder 5 MHz scanner (SonolinePrima, Siemens); Uterine length > 3.4 cm and ovarian volume > 2.0 mL are consistent with precocious puberty [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Bone age: Bone age was measured according to the method presented by Greulich and Pyle [ 20 ]; 2 years above the mean for chronological age is consistent with precocious puberty.…”
Section: Methodsmentioning
confidence: 99%
“…They observed that the adductor sesamoid development was closely related to SOS development. On the contrary, Ebrahimzade et al 23 did not find the Greulich‐Pyle method in hand‐wrist radiographs of the Iranian population accurate enough for age determination in males. Therefore, inadequacy and conflict of population‐based information and increasing demand for age estimation in orthodontics and forensic medicine necessitate further studies on the efficacy of different age estimation methods in various population groups.…”
Section: Discussionmentioning
confidence: 93%